(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The concept of quality of auditing profession comes on top of the concerns of the international business community and international institutions particularly now following the impact of the several failures and financial hardships suffered by the major companies in the recent collapse of money markets in some countries of the world and fear of their recurrence in the future.An observer of the local and international rules and standards (or principles) finds that these include such implications have direct or indirect effects on the performance of the service of the accountant and auditor, which should upgrade their professional performance in these services to a high level of quality so as to be in line with the requirements, principles and nature of the companies.Based on the above, particular research studies as well as professional recommendations produced in the developed world have recently produced to shed some light on as how to measure and evaluate service performance of audit profession; taking into account that whenever the quality of such service is realized, it would automatically be reflected on boosting the accountant performance too. In this connection, several conflicting methods have been developed to control the quality of auditors’ professional performance.Iraq is one of the states in which regulatory bodies of the external audit profession have been established. In response to the requirements of international auditing standards on audit quality as represented in standards (1) and (220), applied research has been developed in an effort to study the reality and role of bodies regulating external audit in the Republic of Iraq in terms of achieving the required level of quality audit and identifying the obstacles that prevented achieving effective quality control over auditors’ offices and Board of Supreme Audit as in accordance with the International Standards on Auditing. The research focuses on the role of these bodies in terms of achieving quality audit by way of implementing a quality control system the benefits of which would go to the beneficiaries of the audits, reduce chances of criticisms and weaknesses, and make it easily acceptable in auditing environment in Iraq.The research is based on a key premise which is lack of coordination between the Council of Audit Control Profession, and the Council of Audit and Control Standards, which affects auditors’ commitment to quality control standards.The researcher concluded to a set of conclusions, the most significant of which are: • Lack of quality control standard required to be applied by auditors. • Weak coordination between the Council of Audit Control Profession, the Association of Accountants and Auditors and the Council of Audit and Control Standards after the year (2003) in the field of quality control of auditors professional performance. • The ceasing of the function of the Council of Audit and Control Standards after (2003) incidents and up to late (2010) when it has been reactivated had a clear impact on not keeping pace with the progress in auditing profession, especially in the field of quality control performance of audit profession in Iraq. The researcher made several recommendations, such as: • Issuance of standard quality control by the Council of Audit and Control Standards in the Republic of Iraq to include two models, the first on the internal organization of the offices of auditors, and the second on program of quality control, as proposed in the study. • Establishment of a regulatory unit for quality control at the Council of Audit Control Profession in the Republic of Iraq by adopting the model of the American Institute of Certified Acts (AICPA). • Activation of the Council of Audit and Control Standards in the Republic of Iraq in relation to issue of standards that keep pace with developments in the field of accounting, auditing and international standards related thereto.